What are the landmarks in a community music project? The case of the Kithara Project - Mateos-Moreno, Daniel (Routledge, 2022)
The “Kithara Project” is an international, non-profit community music programme serving the USA and Mexico. It focuses on a single musical instrument and genre, i.e., classical guitar, and is run by a collective of internationally acclaimed musicians. This chapter introduces the Kithara Project to the research literature and investigates the construction of project landmarks based on the successes and challenges identified by its practitioners. I discuss how the results support, complement, and challenge the existing conceptions in community music before offering practical implications for successful community music practice, including how to achieve a ‘symbiosis’ with the researchers’ world.
Keywords: Música; Kithara; Guitar; Classical; Community; Music